2018
DOI: 10.22268/ajpp-036.3.223230
|View full text |Cite
|
Sign up to set email alerts
|

Primary evaluation of Acibenzolar-S-Methyl (ASM) efficiency on vegetative parameters and resistance responses of tomato and eggplant to root-knot nematode Meloidogyne incognita

Abstract: Mouhanna, A.M. 2018. Primary evaluation of Acibenzolar-S-Methyl (ASM) efficiency on vegetative parameters and resistance responses of tomato and eggplant to root-knot nematode Meloidogyne incognita.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
2
1
0
Order By: Relevance
“…The reason may be due to the efficiency of this isolate in parasitism the eggs of nematodes, which led to a reduction in the galling index and number of galls on the root system, especially that this experiment was carried out at a temperature of 30 ± 5 °C, which is ideal for the growth of the fungus and its ability to infect the eggs of root knot nematodes, and this applies with previous studies [3,10,14]. It is also observed from (Table 2) that all isolates of P. lilacinus achieved a significant reduction in the average number of egg masses on the roots system compared with the control treatment after five weeks of adding the nematode inoculation.Fungi that parasitism of the eggs of root-knot nematodes play a major role in biological control, especially the types of nematodes that lay their eggs together in a gelatinous matrix as root-knot nematode [11,1,9]. This agrees with what [11] found that the fungus P.…”
Section: Effect Of Different Isolates Of P Lilacinus On Meloidogyne J...supporting
confidence: 85%
See 2 more Smart Citations
“…The reason may be due to the efficiency of this isolate in parasitism the eggs of nematodes, which led to a reduction in the galling index and number of galls on the root system, especially that this experiment was carried out at a temperature of 30 ± 5 °C, which is ideal for the growth of the fungus and its ability to infect the eggs of root knot nematodes, and this applies with previous studies [3,10,14]. It is also observed from (Table 2) that all isolates of P. lilacinus achieved a significant reduction in the average number of egg masses on the roots system compared with the control treatment after five weeks of adding the nematode inoculation.Fungi that parasitism of the eggs of root-knot nematodes play a major role in biological control, especially the types of nematodes that lay their eggs together in a gelatinous matrix as root-knot nematode [11,1,9]. This agrees with what [11] found that the fungus P.…”
Section: Effect Of Different Isolates Of P Lilacinus On Meloidogyne J...supporting
confidence: 85%
“…It is also observed from (Table 2) that all isolates of P. lilacinus achieved a significant reduction in the average number of egg masses on the roots system compared with the control treatment after five weeks of adding the nematode inoculation.Fungi that parasitism of the eggs of root-knot nematodes play a major role in biological control, especially the types of nematodes that lay their eggs together in a gelatinous matrix as root-knot nematode [11,1,9]. This agrees with what [11] found that the fungus P.…”
Section: Effect Of Different Isolates Of P Lilacinus On Meloidogyne J...supporting
confidence: 85%
See 1 more Smart Citation